2021
DOI: 10.3390/ijms221910780
|View full text |Cite
|
Sign up to set email alerts
|

Human Liver Stem Cell Derived Extracellular Vesicles Alleviate Kidney Fibrosis by Interfering with the β-Catenin Pathway through miR29b

Abstract: Human liver stem-cell-derived extracellular vesicles (HLSC-EVs) exhibit therapeutic properties in various pre-clinical models of kidney injury. We previously reported an overall improvement in kidney function following treatment with HLSC-EVs in a model of aristolochic acid nephropathy (AAN). Here, we provide evidence that HLSC-EVs exert anti-fibrotic effects by interfering with β-catenin signalling. A mouse model of AAN and an in vitro pro-fibrotic model were used. The β-catenin mRNA and protein expression, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Furthermore, HLSC-EVs expressed mesenchymal markers CD29, CD44, and CD105, but did not express endothelial (CD31), hematopoietic (CD45, CD3, CD8, etc. ), or epithelial (CD24 and CD326) markers [data not shown], as previously reported [36][37][38]. Nanoparticle tracking analysis on EVs revealed the typical size distribution of exosomes and shedding vesicles and transmission electron microscopy analysis confirmed that the EVs had a homogeneous pattern of nanosized membrane vesicles (Figure 1B).…”
Section: Hlsc-evs Improve Kidney Function and Morphology Of Iri-ckd Micesupporting
confidence: 84%
“…Furthermore, HLSC-EVs expressed mesenchymal markers CD29, CD44, and CD105, but did not express endothelial (CD31), hematopoietic (CD45, CD3, CD8, etc. ), or epithelial (CD24 and CD326) markers [data not shown], as previously reported [36][37][38]. Nanoparticle tracking analysis on EVs revealed the typical size distribution of exosomes and shedding vesicles and transmission electron microscopy analysis confirmed that the EVs had a homogeneous pattern of nanosized membrane vesicles (Figure 1B).…”
Section: Hlsc-evs Improve Kidney Function and Morphology Of Iri-ckd Micesupporting
confidence: 84%
“…A previous paper suggests that endothelial β-catenin signaling is a promoting factor in angiogenesis [31]. In addition to being an angiogenic factor, it has been also reported that β-catenin is involved for collagen synthesis [32,33]. Further analyses on Wnt/β-catenin signaling will reveal molecular mechanisms of CC formation under androgen signaling.…”
Section: Discussionmentioning
confidence: 95%
“…Camussi Giovanni (corresponding author) from the Department of Medical Sciences, University of Turin, was the top 5 prolific author for EVs in kidney disease. He mainly focused on the association of EVs with kidney-related diseases (AKI, CKD, systemic lupus erythematosus, ANCA-vasculitis, kidney fibrosis, and diabetic nephropathy) (Biancone and Camussi, 2014;Collino et al, 2015;Lener et al, 2015;Bussolati and Camussi, 2017;Dimuccio et al, 2020;Grange et al, 2020;Kholia et al, 2020;Ramírez-Bajo et al, 2020;Tetta et al, 2020;Kholia et al, 2021;Mazzariol et al, 2021;Bruno et al, 2022;Franzin et al, 2022). Additionally, Cortes Perez-Hernandez et al, 2016;Perez-Hernandez et al, 2017;Perez-Hernandez et al, 2018a;Perez-Hernandez et al, 2018b;Olivares et al, 2018;Olivares et al, 2020;Ortega et al, 2020;Perez-Hernandez et al, 2021a;Perez-Hernandez et al, 2021b;Redon et al, 2021;Martinez-Arroyo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Camussi Giovanni (corresponding author) from the Department of Medical Sciences, University of Turin, was the top 5 prolific author for EVs in kidney disease. He mainly focused on the association of EVs with kidney-related diseases (AKI, CKD, systemic lupus erythematosus, ANCA-vasculitis, kidney fibrosis, and diabetic nephropathy) ( Biancone and Camussi, 2014 ; Collino et al, 2015 ; Lener et al, 2015 ; Bussolati and Camussi, 2017 ; Dimuccio et al, 2020 ; Grange et al, 2020 ; Kholia et al, 2020 ; Ramírez-Bajo et al, 2020 ; Tetta et al, 2020 ; Kholia et al, 2021 ; Mazzariol et al, 2021 ; Bruno et al, 2022 ; Franzin et al, 2022 ). Additionally, Cortes Raquel (corresponding author) from the Cardiometabolic and Renal Risk Research Group, INCLIVA Biomedical Research Institute, was the top 4 prolific author for EVs in kidney-related diseases.…”
Section: Discussionmentioning
confidence: 99%